Production and perception of legato, portato, and staccato articulation in saxophone playing - Hofmann, Alex; Goebl, Werner (Frontiers in Psychology, 2014)
This paper investigates the production and perception of different articulation techniques on the saxophone. In a production experiment, two melodies were recorded that required different effectors to play the tones (tongue actions alone, finger actions alone, combined tongue and finger actions) at three different tempi. A sensor saxophone reed was developed to monitor tongue-reed interactions during performance. At the slow tempo condition, combined tongue-finger actions showed improved timing, compared to the timing of the tongue alone. This observation supports the multiple timer hypothesis where the tongue's timekeeper benefits from a coupling to the timekeeper of the fingers. At the fast tempo condition, finger alone actions were less precise than the tongue alone and combined tongue-finger actions led to more variable timing. This suggests that the finger actions have a dominant influence on the overall timing of saxophone performance. In a listening experiment we investigated whether motor expertise in music performance influences the perception of articulation techniques in saxophone performance. Participants with different backgrounds in music making (saxophonists, musicians not playing the saxophone, and non-musicians) attended an AB-X listening test. They had to discriminate between saxophone phrases played with different articulation techniques (legato, portato, staccato). Participants across all three groups discriminated the sound of staccato articulation well from the sound of portato articulation and legato articulation. Errors occurred across all groups of listeners when legato articulation (no tonguing) and portato articulation (soft tonguing) had to be discriminated. Saxophonists' results were superior compared to the results of the other two groups, suggesting that expertise in saxophone playing facilitated the discrimination task.